2012
DOI: 10.2500/ajra.2012.26.3710
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Therapy in the Treatment of Chronic Rhinosinusitis: A Meta-Analysis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 36 publications
0
31
0
2
Order By: Relevance
“…8 Se desarrolló interés creciente por el manejo de estos pacientes con antifúngico sistémico como itraconazol, con base en el beneficio que reportaba para pacientes con ABPA; 9 sin embargo, su eficacia en RAF no ha sido establecida y actualmente no se recomienda su uso. 10 Por otro lado, la inmunoterapia se ha convertido de forma reciente en una herramienta terapéutica valiosa en estos pacientes, segura y efectiva, con la capacidad de disminuir las dosis de esteroide tópico sistémico y las tasas de re-intervención. 11 El paciente reportado inició tratamiento con inmunoterapia específica subcutánea y continúa hasta la fecha de elaboración de este reporte con fluticasona.…”
Section: Discussionunclassified
“…8 Se desarrolló interés creciente por el manejo de estos pacientes con antifúngico sistémico como itraconazol, con base en el beneficio que reportaba para pacientes con ABPA; 9 sin embargo, su eficacia en RAF no ha sido establecida y actualmente no se recomienda su uso. 10 Por otro lado, la inmunoterapia se ha convertido de forma reciente en una herramienta terapéutica valiosa en estos pacientes, segura y efectiva, con la capacidad de disminuir las dosis de esteroide tópico sistémico y las tasas de re-intervención. 11 El paciente reportado inició tratamiento con inmunoterapia específica subcutánea y continúa hasta la fecha de elaboración de este reporte con fluticasona.…”
Section: Discussionunclassified
“…Within the review, sixteen of the included studies reported objective outcomes in the form of endoscopic findings. The endoscopic findings were either reported as part of validated scoring scales (1,7,(16)(17)(18)(19)21,22,(25)(26)(27)(28) or nonvalidated systems (15,20,23,24,30) . Seven studies reported endoscopic improvement (15,(17)(18)(19)(22)(23)(24) , whereas the remainder of the studies reported no benefit (endoscopic) from antifungal agents.…”
Section: Discussionmentioning
confidence: 99%
“…Disease specific QOL scores were collated within a meta-analysis (1) , which reported no significant improvement in QOL with the use of topical AMB when compared to the placebo. When assessed individually (without the studies which excluded AFS) there was still no benefit reported.…”
Section: Non-validated Symptom Scoresmentioning
confidence: 99%
“…Amfoterisin B sistemik antifungal tedavide sıklıkla kullanılmasına rağmen nefrotoksik oluşu, elektrolit dengesizliği oluşturması, kullanımdan sonraki ateş titreme, taşipne gibi ciddi yan etkileri kullanımını kısıtlamaktadır (10). Son yıllarda amfoterisin B yerine kullanılan ikinci nesil azol türevlerinden vorikonazol ile sistemik tedavinin başarılı olduğunu gösteren yayınlar mevcuttur (11,12). Vorikonazol candida, aspergillus, kriptokok ve diğer mantar türlerine etkilidir.…”
Section: Discussionunclassified